Grievance procedure for non-teaching employees. - University of the Philippines (Diliman). Human Resources Development Office ([Quezon City UP HRDO, 1996)
The Human Resources Development Office decided to publish this Manual to serve as a guide and ready reference on the issues covered and the process involved in filing and resolving grievances. It contains guiding principles, implementing guidelines, miscellaneous provisions, schematic diagram of the grievance procedure and application.
Cover title.
Keywords: University of the Philippines -- Employees; University of the Philippines; Grievance procedures -- Philippines -- Quezon City